(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The research aims to build a training program to develop some executive functions for kindergarten children. To achieve this goal, the two researchers built the program according to the following steps: 1. Determining the general objective of the program. 2. Determining the behavioral objectives of the program. 3. Determining the included content in the program. 4. Implementing the content of the activities of the program. 5. Evaluating the Program. The program included (12) training activities, the training activities included several items: the title of the activity, the time of implementation of the activity, the general objective of the activity, the procedural behavioral objective, the means and tools used, the methods and techniques, the content, the implementation of the activity, and the evaluation.